Pedicled jejunal interposition as esophageal substitute in pediatric patients. Technical considerations and long-term results - Antonio Dessanti; Diego Falchetti; Vincenzo Di Benedetto; Maria Grazia Scuderi (Elsevier, 2021)
The current study reports the surgical technique and the clinical long term results of pediatric esophageal substitution with a pedicled jejunal loop in two patients with long gap esophageal atresia and one patient with severe esophageal stenosis due to a caustic lesions. Postoperative course was uneventful in all patients. At a long term follow-up of 29 and 43 years for the patients with esophageal atresia and 21 for the one with caustic stenosis, no feeding troubles were reported due to malfunction of the esophageal replacement nor to loss of its original functions and the patients referred a highly satisfying quality of life. Pedicled jejunal interposition confirms as a good substitute of the esophagus in pediatric age with the advantage to maintain good performances for very long time. Although these patients do not share the same risks of illness as other patients still harboring their native pathologic esophagus, a far sighted surveillance is recommended due to long term potential morbility risk.